Perlindungan Hukum Pasien Bpjs Kesehatan Atas Pelayanan Kesehatan Rumah Sakit Berdasarkan Undang-Undang Nomor 24 Tahun 2011 Tentang Badan Penyelenggara Jaminan Sosial - Abdun Nadhif (Lembaga Pengembangan Kinerja Dosen, 2023)
Health insurance or health care insurance is an attempt to create risk pooling, namely transferring personal risk to group risk so that risk sharing occurs. In health insurance, the costs are shared by the community through a pre-effort contribution system. The goal of health insurance is to improve health care services for participants and their families. Health insurance also aims to provide assistance to participants in financing their health care.